Dust grains charging of low temperature dusty plasmas under ion acoustic parametric instability onset - Olshansky, V.V. (Вопросы атомной науки и техники, 2016)
The process of dust grains charging in low temperature dusty plasmas of low pressure is considered under parametric ion acoustic instability development. The secondary electron emission from the dust grain surface and a dust grain polarization under the action of the self-consistent electric field are taken in account. The results of the numerical 2D3V simulation of dusty plasmas charging in RF discharge are presented in cylindrical geometry. For self-consistent simulation of dust grain charging process we use the numerical model that comprises three models: «Particle-in-Cell» (PIC), «Monte Carlo Collisions» (MCC) and «Particle-Particle Particle-Mesh» (P3M) models.